17 Anemia in juvenile idiopathic arthritis: analysis of associated factors. (7th October 2022) - Tbini, Houssem; Rahmouni, Safa; Boussaid, Soumaya; Ammou, Ahlem Ben; Jemmali, Samia; Rekik, Sonia; Zouaoui, Khaoula; Sahli, Hela; Elleuch, Mohammed
Abstract: Background: Anaemia is the most frequent hematological disorder in chronic inflammatory rheumatic disease. Few studies have focused on this impairment in juvenile idiopathic arthritis (JIA). Objectives: To identify the factors associated with anaemia in JIA. Methods: We conducted a retrospective study including adults with long-standing JIA according to the International League of Associations for Rheumatology (ILAR) criteria over a period of 28 years (1994–2022). Demographic, clinical, biological, and radiographic data were collected. These parameters were compared according to the presence or absence of anaemia. Results: Seventeen women and 12 men were enrolled. The mean age was 35.69 ± 11.72 [18–61] years. The mean age of disease onset was 11.10 ± 4.25 [2–16] years. The average diagnostic delay was 52.96 ± 95.97 [0–336] months. The average disease duration was 24.48 ± 12.76 [1–47] years. The polyarticular form was the most frequent ( n = 16). Rheumatoid factor, ACPA and antinuclear antibodies were present in 41.4%, 24.1% and 17.2% of cases respectively. Mean CRP values were 42.74 ± 63.37 [2–218] mg/l, a biological inflammatory syndrome was present in 19 cases. NSAIDs, corticosteroids and methotrexate were used in 62.1% ( n = 18), 69% ( n = 20) and 79.3% ( n = 23) respectively. Anaemia was noted in 69% ( n = 20) of cases, it was hypochromic in 8 cases and microcytic in 11 cases. The mean haemoglobin value was 11.31 2.10 [6.5–15] g/dl. Anaemia was associated with the following parameters in our study: female sex (88.2% vs 41.7%; p = 0.008), absence of anti-nuclear antibodies (76.9% vs 20%; p = 0.026) and corticosteroid therapy (85% vs 33.3%; p = 0.005). However, the comparison of patients according to the presence of anaemia did not show any significant difference for these parameters: age, age at onset, diagnostic delay, duration of symptoms, extra-articular manifestations, CRP value, presence of biological inflammatory syndrome, rheumatoid factor, ACPA, erosive nature and treatment (NSAIDs and methotrexate). Conclusion: Anaemia is common in JIA. Its treatment is part of the overall management of the disease.